Effect of progesterone administration on the prognosis of patients with severe traumatic brain injury: a meta-analysis of randomized clinical trials - Pan ZY; Zhao YH; Huang WH; Xiao ZZ; Li ZQ (Drug Design, Development and Therapy, 2019)
Zhi-Yong Pan, Yu-Hang Zhao, Wen-Hong Huang, Zhi-Ze Xiao, Zhi-Qiang Li Department of Neurosurgery, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, PR China Purpose: The aim of this study was to assess the neuroprotective effect of progesterone administration on severe traumatic brain injury (TBI) for different follow-up periods and administration route by completing a meta-analysis of randomized clinical trials (RCTs).Methods: A systematic literature search of PubMed, Embase, and Cochrane databases and the Web of Science (from establishment of each to September 1, 2018) was performed to identify original RCTs that evaluated the associations between progesterone treatment and the prognosis of patients with severe TBI.Results: Eight RCTs enrolling 2,251 patients with severe TBI were included. Within 3 months post-injury, patients with progesterone administration had a lower mortality (risk ratio [RR] =0.59; 95% CI [0.42–0.81], P=0.001) and better neurologic outcomes (RR =1.51; 95% CI [1.12–2.02], P=0.007) than those who received placebo. However, these differences did not persist at 6 months post-injury for mortality (RR =0.96; 95% CI [0.65–1.41], P=0.83) or neurologic outcomes (RR =1.09; 95% CI [0.93–1.27], P=0.31). The analysis stratified by administration route showed that beneficial effects were only observed in patients who received progesterone intramuscularly (RR =1.61, 95% CI [1.19–2.18], P=0.002); no benefit was observed with intravenous administration (RR =0.99, 95% CI [0.91–1.07], P=0.75).Conclusion: Progesterone administration improved the clinical outcomes of severe TBI patients within 3 months but may not have significant long-term benefits 6 months post-injury. Keywords: progesterone, severe traumatic brain injury, neuroprotection